Knowledge of sensory processing disorder among special education teachers in primary school at Melaka Tengah/ Ahmad Kamal Mohd Natar, Anis Farhana Abd Rashid - Mohd Natar, Ahmad Kamal; Abd Rashid, Anis Farhana (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
This study is about sensory processing disorders and also to identify the differences of familiarity with the strategies and resources to support children with SPD between special education teachers in urban and rural areas. Using a cross-sectional study, 118 special education teachers participated in this study and answered the Demographic Profile and the Questionnaire for SENCOs. Most of the participants rated for 'unsure' and 'disagree' (79%) that indicated that they were lacking in understanding about SPD. There were no differences between the understanding of SPD and gender, teaching experience, and the location of the school. However, there was a difference between the understanding of SPD and the level of education and the presence of family with SPD (p=.036 HAT). Also, there was no association between the teaching experiences and the confidence in identifying behavior caused by sensory and the familiarity with the strategies and resources to support children between special education teachers in urban and rural areas. This study indicates that most of the special education teachers which involve in special education school lack in understanding of SPD.